648. Urinary Tract-Associated Escherichia coli Bacteraemia Strains Are Genetically More Virulent than Those Originating From Non-urinary and Neutropaenic Infective Foci. (26th November 2018) - Dale, Adam; Pandey, Anish; Hesp, Richard; Belogiannis, Konstantinos; Laver, Jay; Shone, Clifford; Read, Robert
Abstract: Background: Escherichia coli is the leading cause of bacteremia with multi-drug-resistant strains proving increasingly problematic. Knowledge of the strain diversity associated with site-specific infections will inform the development of new preventative strategies, e.g. vaccines. We hypothesized that virulence factor (VF) scores of bacteremia strains from neutropenia patients with unknown infective foci (NPUIF—likely due to bowel translocation) would be lower than those from immunocompetent patients. Methods: Immunocompetent ( n = 49) and neutropaenic adults ( n = 8) with E. coli bacteremia were prospectively enrolled and the focus of bacteremia determined. Neutropenia patients were enrolled only if there was no identifiable infective focus. Multi-locus sequence typing and VF score (31 known VFs included) data were derived in silico following whole-genome sequencing and the results compared between patient groups. Results: Bacteremia strains from immunocompetent patients with urinary tract infective foci (UTI-foci) harbored significantly more VFs (median VF score 16, range 8–24) than strains from both immunocompetent patients with non-UTI-foci (10, 2–22, P = 0.006) and NPUIF (8, 3–13, P < 0.0001). VF scores of strains from non-UTI-foci were not significantly different to those from NPUIF (10, 2–22 vs. 8, 3–13, respectively. P = 0.28). Logistic regression analysis demonstrated that VF score (OR 1.21, 95% CIs 1.01–1.46, P = 0.039) and recurrent urinary tract infection/urinary tract infection (OR 12.82, 95% CIs 1.24–132.65, P = 0.032) were independent predictors of bacteremia secondary to UTI-foci vs. non-UTI-foci in immunocompetent patients. Hence, for every unit increase in VF score, the odds of a bacteremia strain originating from UTI-foci increased by 1.21. papA, papC, papE/F, papG, agn43, tia, iut, fyuA, kpsM and sat were significantly more prevalent amongst strains associated with UTI-foci vs. non-UTI-foci amongst immunocompetent patients. papC, papE/F, papG, agn43, tia, fyuA, hlyA, usp and clb were significantly more prevalent amongst UTI-foci- vs. NPUIF-associated strains. Conclusion: UTI-associated E. coli bacteremia strains have distinct VF profiles from those originating from non-UTI-foci and NPUIF. Future vaccines must consider this diversity to ensure adequate coverage of strains associated with site-specific disease. Disclosures: All authors: No reported disclosures.